2007
DOI: 10.1007/s10067-007-0787-7
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a traditional therapeutical approach in early psoriatic arthritis: results of a pilot randomised 6-month trial with methotrexate

Abstract: Thirty-five patients with Early Psoriatic Arthritis (EPA) (17 female and 18 male; mean age 25.6 years) entered this randomised 6-month study. At the enrolment, all patients were on non-steroidal anti-inflammatory drug (NSAID) therapy on demand and were divided in two matched groups (A and B). Group A continued NSAID therapy at full dosage in the following 3 months and then added methotrexate (MTX) for another 3 months. Group B was under the combination of NSAID and MTX for the entire 6-month period. Clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 7 publications
0
40
1
2
Order By: Relevance
“…14 None of the subjects in the case group were on nonsteroidal antiinflammatory drugs or prednisone at the time of the study, nor were any of them receiving combined treatments (TNF-␣ blockersϩDMARDs). All PsA subjects had a clinically active disease (evaluated by the Physician Global Assessment) 15 before being treated with 1 of the 2 treatment schedules. In addition to individual treatment schedules, a trained staff member evaluated disease duration and inflammation indices (erythrocyte sedimentation rate [ESR], C-reactive protein [CRP], and interleukin 6 [R&D Systems Inc, Minneapolis, Minn]) levels.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…14 None of the subjects in the case group were on nonsteroidal antiinflammatory drugs or prednisone at the time of the study, nor were any of them receiving combined treatments (TNF-␣ blockersϩDMARDs). All PsA subjects had a clinically active disease (evaluated by the Physician Global Assessment) 15 before being treated with 1 of the 2 treatment schedules. In addition to individual treatment schedules, a trained staff member evaluated disease duration and inflammation indices (erythrocyte sedimentation rate [ESR], C-reactive protein [CRP], and interleukin 6 [R&D Systems Inc, Minneapolis, Minn]) levels.…”
Section: Methods Subjectsmentioning
confidence: 99%
“…Results suggested some efficacy on joints and skin, but findings were inconclusive, in particular in view of small study numbers. [80][81][82] 221 active PsA patients. 83 The trial took several years to complete, and results showed no evidence that MTX improved synovitis compared to placebo.…”
Section: Disease-modifying Antirheumatic Drugs In Psamentioning
confidence: 99%
“…Only Scarpa in 2008 conducted a study on effect of traditional DMARDs in eSpa: 35 ePsA treated for six months with low dosage of methotrexate (10 mg weekly) were followed up with routine clinical and laboratory examination 25 .…”
Section: Treatmentmentioning
confidence: 99%